Reframing Learning Quality in Higher Education: A TQM-Based Approach in Research and Evaluation Courses - Wahyudin Rajab; Aan Nurhasanah; Nana Mulyana; Andi Sari Bunga Untung; Safrudin Safrudin (JUMPA : Jurnal Manajemen Pendidikan, 2026)
This study examines how Total Quality Management (TQM) is implemented within the learning process of the Research and Educational Evaluation (PEP) course and how it influences learning quality in higher education. The study responds to ongoing concerns regarding the limited effectiveness of conventional teaching approaches in developing students’ analytical and research competencies. A qualitative case study design was employed, involving 40 participants including lecturers, students, quality assurance representatives, technical staff, and alumni. Data were collected through in-depth interviews, field findings, and document analysis, and analyzed using a thematic approach based on the interactive model of Miles, Huberman, and Saldana. The findings reveal that the implementation of TQM led to noticeable changes in learning design, instructional practices, and feedback mechanisms. Learning became more participatory, with students actively engaged in research-related tasks and practical activities. The involvement of multiple stakeholders also contributed to a more responsive learning environment, forming what can be understood as a learning ecosystem. At the same time, these improvements were accompanied by challenges, particularly increased workload and the need for adaptation among students and lecturers. These results suggest that improving learning quality requires not only structured frameworks but also continuous interaction and support across stakeholders. The study highlights the importance of viewing quality management as a process embedded in everyday learning practices rather than as a purely administrative system.